An Analysis Upon Various Policies to Enhance Fundamental Abilities of Low Scoring Students In Secondary Education Schools In India: Addressing Inequalities and Improving Access to Secondary Education in India (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Secondary education’s contribution to economic growth, demonstratedhigh social benefits (particularly for girls), and support of democraticcitizenship reinforce the need for increased public support at this level,particularly in light of the very large inequalities in access to secondaryeducation, by income, gender, social group and geography. The challenge is to dramatically improve access, equity and quality ofsecondary education simultaneously. Government has an important role to play inimproving equity of secondary education. The bulk of the growth in secondaryeducation over the last ten years has been financed by households for privateschooling, such that the typical secondary school student is male, urban andmiddle class. Whether because of poverty, credit constraints, lack ofinformation about perceived benefits of schooling, cultural norms or otherfactors, access to secondary education by girls and by children from scheduledcastes, scheduled tribes, rural and poor households is significantly lower thanstate and national averages. Indicators of internal efficiency and quality oflearning among these groups are also well below average. Targeted, supply- anddemand side programs for these groups are called for. The recently launched centrally sponsored scheme for secondaryeducation, Rashtriya Madhyamik Shiksha Abhiyan (RMSA), offers a strategicopportunity to improve access and equity; enhance quality, accountability andability to measure learning outcomes; and promote standardization of curriculumand examinations across states. In addition, India’s recent decision toparticipate in international assessments of student achievement is an extremelypositive sign. Over time, such participation will provide an importantobjective baseline of students’ cognitive skills and a future measure ofsuccess of the country’s investments in elementary and secondary education.